Deciding to decide: gender, leadership and risk-taking in groups - Seda Ertac; Mehmet Yigit Gurdal (TÜSİAD-Koç University Economic Research Forum, 2010)
Being the leader in a group often involves making risky decisions that affect the payoffs of all members, and the decision to take this responsibility in a group is endogenous in many contexts. In this paper, we experimentally study: (1) the willingness of men and women to make risky decisions on behalf of a group, (2) the amount of risk men and women take for the group, in comparison to their individual decisions. We observe a striking difference between males and females, with a much lower fraction of women being willing to make the group decision than men. The amount of risk taken for the group is generally lower than in the case where subjects decide for themselves only, indicating a cautious shift. The women that would like to make the group decision and the women that do not are no different in terms of how much risk they take for themselves, nor for their group. For men, on the other hand, we find that the ones who would like to lead tend to take more risk on behalf of the group. We also present several results on the relationship of risk-taking and leadership decisions with personality traits.
Keywords: C91; C92; D81; J16; 330; gender; group decision-making; risk; leadership; experiments; Gruppenentscheidung; Entscheidung bei Risiko; Geschlecht; Führungspersönlichkeit; Test